2003
DOI: 10.1590/s1677-55382003000100005
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of 6- and 12-punctures biopsies to detect prostate cancer in patients with PSA< 10 ng/mL and normal digital rectal examination

Abstract: Objective: Establish the efficiency of 6-and 12-punctures transrectal ultrasound-guided needle biopsies in low risk patients for prostate cancer. Six-punctures (sextant) biopsies were compared to 12-punctures biopsies, assessing which is the best strategy to detect this neoplasm.Materials and Methods: Among 240 patients submitted to prostate biopsy, 54 with suspected small and organ-localized tumors (prostatic specific antigen ≤ 10 ng/mL and digital exam of the prostate not suggesting cancer) in glands < 50 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Generally, in the clinical setting, when a patient is diagnosed as a suspicious prostate cancer sufferer with a high PSA level or an abnormal screening DRE, a biopsy is frequently suggested [56]. Often, when doing a biopsy, the prostate is divided into sections based on the number of biopsy points to use, followed by shooting a needle in each section to extract the respective tissue sample.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Generally, in the clinical setting, when a patient is diagnosed as a suspicious prostate cancer sufferer with a high PSA level or an abnormal screening DRE, a biopsy is frequently suggested [56]. Often, when doing a biopsy, the prostate is divided into sections based on the number of biopsy points to use, followed by shooting a needle in each section to extract the respective tissue sample.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…28.02.4779 in different countries. 5,6,7 However, far from a standardized practice, prostate biopsy is still evolving. Indeed.…”
Section: Introductionmentioning
confidence: 99%
“…The common protocol used in TRUS guided prostate biopsy is sextant biopsy proposed by Hodge et al in the late eighties ( 16 , 17 ). However in the last decade, several studies were designed to evaluate prostate cancer detecting performance by TRUS guided prostate biopsy with more than six biopsies either from other sites of prostate or repeating biopsy in the six previous areas ( 18 - 21 ). The results of studies confirmed the hypothesis that greater numbers of biopsies increases the diagnostic power.…”
Section: Introductionmentioning
confidence: 99%